2022
DOI: 10.1002/admi.202200177
|View full text |Cite
|
Sign up to set email alerts
|

1.1‐Millimeter Tall Vertically Aligned‐Carbon Nanotubes Grown by Cold Wall CVD Using a Novel Multiple‐Purge Method

Abstract: These processes still have limitation in achieving high yield and quality, and any commercial use of CNTs is limited due to these challenges encountered in large scale synthesis. [17] According to Shi et al. (2017), [18] "The poor reproducibility in CNT synthesis via CVD has been attributed to fluctuations in ambient and reactor-sorbed water vapor, as well as to carbonaceous deposits inside reactors leading to growth hysteresis." The presence of water or oxygen influences the growth gases and contributes to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The height at the catalyst composition of 3:2 at 650 °C could not be determined from the SEM image, but it can be assumed that following the trend stated before, the carbon nanotubes at this ratio are higher than at 700 °C. In contrast to other studies 44 48 , where the aim was to produce higher VACNTs, in the present work short carbon nanotubes were grown, with the advantage of short carbon nanotubes having better thermal conductivity 49 . It was revealed that the highest VACNTs (9.0 µm and 8.7 µm) were obtained in case of Fe:Co 2:3 at 650 °C and Fe:Co 1:3 at 700 °C, which is an additional difference from the published results is that the highest carbon nanotubes were not formed at the 1:1 catalyst composition 50 .…”
Section: Resultsmentioning
confidence: 93%
“…The height at the catalyst composition of 3:2 at 650 °C could not be determined from the SEM image, but it can be assumed that following the trend stated before, the carbon nanotubes at this ratio are higher than at 700 °C. In contrast to other studies 44 48 , where the aim was to produce higher VACNTs, in the present work short carbon nanotubes were grown, with the advantage of short carbon nanotubes having better thermal conductivity 49 . It was revealed that the highest VACNTs (9.0 µm and 8.7 µm) were obtained in case of Fe:Co 2:3 at 650 °C and Fe:Co 1:3 at 700 °C, which is an additional difference from the published results is that the highest carbon nanotubes were not formed at the 1:1 catalyst composition 50 .…”
Section: Resultsmentioning
confidence: 93%